2006
DOI: 10.1136/vr.159.1.7
|View full text |Cite
|
Sign up to set email alerts
|

Serological responses of adult dogs to revaccination against distemper, parvovirus and rabies

Abstract: Serum antibody titres to canine distemper virus (CDV), canine parvovirus (CPV) and rabies were measured in dogs that had not been revaccinated annually and compared with the titres in a control group of regularly vaccinated animals; 83 per cent (171 of 207) of the dogs vaccinated against CDV one or more years earlier had serum neutralising antibody titres equal to or greater than 16; 64 per cent (136 of 213) of the dogs vaccinated against CPV one or more years earlier had haemagglutination inhibiting titres eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
22
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 22 publications
(6 reference statements)
5
22
0
Order By: Relevance
“…33,34 As measurement of memory cells is not practical, based on this theory, it has been suggested that the ability to detect any antibody titre in a previously vaccinated and actively immune animal demonstrates that memory effector B cells are present and functional, and that this correlates with protective immunity. 11,19,20,[23][24][25] The general consensus from these studies is that MLV vaccination against the core canine viral diseases generally confers reliable multi-year protection. 12,28,35 Additionally, it has been advised that testing for antibody status is a better practice than simply administering a vaccine booster on the basis that this should be safe and costs less.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…33,34 As measurement of memory cells is not practical, based on this theory, it has been suggested that the ability to detect any antibody titre in a previously vaccinated and actively immune animal demonstrates that memory effector B cells are present and functional, and that this correlates with protective immunity. 11,19,20,[23][24][25] The general consensus from these studies is that MLV vaccination against the core canine viral diseases generally confers reliable multi-year protection. 12,28,35 Additionally, it has been advised that testing for antibody status is a better practice than simply administering a vaccine booster on the basis that this should be safe and costs less.…”
Section: Discussionmentioning
confidence: 99%
“…The antibody titre data generated from this study are similar to those generated in similar studies performed elsewhere. 11,19,20,[23][24][25] The general consensus from these studies is that MLV vaccination against the core canine viral diseases generally confers reliable multi-year protection. Additionally, since 2003 the recommendation of vaccination guidelines groups has been that the DOI induced by MLV core canine vaccines is beyond 12 months and that revaccination with these vaccines should not occur more frequently that every 3 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results can only demonstrate antibody titres at that one particular moment in time 15 . It is currently impossible to predict antibody titres for any forthcoming period for the individual animal, although one study found no significant antibody decrease over time 16 …”
Section: … and The Disadvantagesmentioning
confidence: 99%